A SURREAL LANDSCAPE OF DEVASTATION: AN ANALYSIS OF LEE MILLER’S GRIM GLORY PHOTOGRAPHS OF THE LONDON BLITZ (Revue D’études Interculturelles De L’image, 2013)
As surrealist war documents, Lee Miller’s war photographs of the London Blitz, published in Ernestine Carter’s Grim Glory: Pictures of Britain Under Fire (1941), effectively demonstrate what Susan Sontag referred to as “a beauty in ruins”. Miller’s Blitz photographs may be deemed aesthetically significant by considering her Surrealist background and by analyzing her images within the context of André Breton’s theory of “convulsive beauty”. Therefore, this essay aims to demonstrate how Miller’s photographs not only depict the chaos and destruction of Britain during the Blitz, they also expose Surrealism’s love of strange, evocative or humorous juxtapositions in the form of artistic visual representations of a temporary surreal landscape filled with fallen statues and broken typewriters.